The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1371/journal.pone.0170038
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in Splicing Factor Genes Are a Major Cause of Autosomal Dominant Retinitis Pigmentosa in Belgian Families

Abstract: PurposeAutosomal dominant retinitis pigmentosa (adRP) is characterized by an extensive genetic heterogeneity, implicating 27 genes, which account for 50 to 70% of cases. Here 86 Belgian probands with possible adRP underwent genetic testing to unravel the molecular basis and to assess the contribution of the genes underlying their condition.MethodsMutation detection methods evolved over the past ten years, including mutation specific methods (APEX chip analysis), linkage analysis, gene panel analysis (Sanger se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 72 publications
4
37
3
Order By: Relevance
“…Previous functional studies have demonstrated that p.Ala615Thr variant is a benign polymorphism, and by itself only slightly affects the enzymatic activity of HGSNAT (Feldhammer, Durand, & Pshezhetsky, ). This change, however, has been linked to the phenotype of retinitis pigmentosa when present in homozygosity or heterozygosity (either in cis or trans ) with other HGSNAT mutations (Comander et al, ; Haer‐Wigman et al, ; Van Cauwenbergh et al, ). p.Ala615Thr shows the highest allele frequency (0.01462 in gnomAD) in the Ashkenazi Jewish population (Table S6B).…”
Section: Resultsmentioning
confidence: 89%
“…Previous functional studies have demonstrated that p.Ala615Thr variant is a benign polymorphism, and by itself only slightly affects the enzymatic activity of HGSNAT (Feldhammer, Durand, & Pshezhetsky, ). This change, however, has been linked to the phenotype of retinitis pigmentosa when present in homozygosity or heterozygosity (either in cis or trans ) with other HGSNAT mutations (Comander et al, ; Haer‐Wigman et al, ; Van Cauwenbergh et al, ). p.Ala615Thr shows the highest allele frequency (0.01462 in gnomAD) in the Ashkenazi Jewish population (Table S6B).…”
Section: Resultsmentioning
confidence: 89%
“…Despite this correlation between splicing factor levels and splicing outcomes during aging, it is not clear whether the decreased expression of splicing factors causes the observed age‐associated changes in splicing. As several splicing factors are mutated in age‐related eye disease, understanding the link between individual splicing regulators and age‐associated changes in splicing could have important implications for human health (Daiger, Sullivan, & Bowne, 2013; Sullivan et al, 2006; Van Cauwenbergh et al, 2017). …”
Section: Introductionmentioning
confidence: 99%
“…Pan et al 19 suggested that patients harboring the mutation c.3260C>T may be associated with a more severe phenotype than patients with the mutation c.2042G>A. We therefore compared the reported symptoms and age at onset, as well the phenotype, of all mutations published to date [4][5][6][7][8][9][10][11][12]19,[27][28][29][30][31][32][33][34][35][36] in Table 5. Reduced vision and night blindness, less often visual field changes, are the most commonly reported symptoms.…”
Section: Discussionmentioning
confidence: 99%